The Impact of Physical Activity on the Clinical Course of Crohn’s Disease: Review - Michalak, Katarzyna; Zukierski, Krystian; Mazur, Michał; Żak, Katarzyna; Jucha, Hubert; Madyniak, Katarzyna; Pliszka, Aleksandra; Kluz, Agnieszka (Quality in Sport, 2025)
Introduction and Aim: Crohn’s Disease (CD) is a chronic inflammatory bowel disease (IBD) characterized by periods of remission and relapse. The influence of lifestyle, particularly physical activity, on the course of IBD is increasingly recognized. This study aims to examine the impact of physical activity on the clinical course of Crohn’s disease and the development of associated complications. Methods and Materials: This research will involve a systematic review of the literature published between 2010 and 2025. Relevant studies will be identified by searching electronic databases including PubMed and Google Scholar databases. The search strategy will utilize a combination of keywords related to Crohn’s disease, physical activity, exercise, and osteopenia. Studies published in English and Polish that examine the effect of exercise interventions on adult CD patients will be included. Studies evaluating the impact of exercise on disease activity, quality of life, bone mineral density, and other relevant outcomes will be considered. The methodological quality of the included studies will be assessed using appropriate tools. Data extraction and synthesis will be performed following established guidelines for systematic reviews. Results and Conclusion: A comprehensive studies review suggests that physical activity can be a valuable tool in managing Crohn’s Disease and preventing complications such as osteopenia. Exercise appears to offer benefits for bone health, mental well-being and overall quality of life of patients with CD. It’s important to note that further research is needed to determine the optimal type, intensity, and duration of exercise for individuals with CD, as well as to identify strategies to promote adherence to exercise programs.